Translational Research of Zoonotic Parasites: Toward Improved Tools for Diagnosis, Treatment and Control - Vito Colella (MDPI AG, 2021)
A range of factors, including social, demographic and economic transformation and human-induced environmental changes, are influencing the emergence or re-emergence of zoonoses, posing new challenges in how we detect, treat and prevent such diseases [...]